2015
DOI: 10.12669/pjms.315.6837
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status of children with congenital heart disease (CHD) attending university of Nigeria teaching hospital ituku – ozalla, Enugu

Abstract: Background and Objectives:Children with congenital heart disease (CHD) are prone to malnutrition. This can have a significant effect on the outcome of surgery. Our objective was to determine the burden and determinant of malnutrition in children with several types of congenital heart disease (CHD).Methods:This is a descriptive cross sectional study of children attending the outpatient clinic of UNTH, Ituku – Ozalla, Enugu State, over a six year period from March 2007 to April 2014. Data analysis was done with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
55
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 12 publications
14
55
1
6
Order By: Relevance
“…The characteristic of subjects in this study were comparable between C-CHD and NC-CHD. This study found most subjects were age 27 months, similar to the study conducted in Jakarta with most subjects in the age range from 0.49 to 24 months, likewise a study conducted in Turkey (Sjarif et al, 2011;Arodiwe et al, 2015). Age is an important factor for CHD natural history that would affect the progression of complications of CHD.…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…The characteristic of subjects in this study were comparable between C-CHD and NC-CHD. This study found most subjects were age 27 months, similar to the study conducted in Jakarta with most subjects in the age range from 0.49 to 24 months, likewise a study conducted in Turkey (Sjarif et al, 2011;Arodiwe et al, 2015). Age is an important factor for CHD natural history that would affect the progression of complications of CHD.…”
Section: Resultssupporting
confidence: 85%
“…Pulmonary hypertension had impact on growth and nutrition, both in cyanotic and acyanotic CHD. Patients with cyanotic and pulmonary hypertension were more affected than patients with acyanotic and pulmonary hypertension (Arodiwe, 2015). Cyanotic patients without pulmonary hypertension and acyanotic patients with pulmonary hypertension had significantly lower weight, height, and head circumference compared to CHD children.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The prevalence of underweight, stunting and wasting in the study of Hassan et al (26) in 2015 in Egypt reported to be 14.3%, 61.9% and 23.8%; but the prevalence of the aforementioned variables in the study of Okoromah et al (9) in 2011 in Nigeria were 20.5%, 28.8% and 41.1%, and the relative proportions of the underweight, stunting and wasting in the study of the Ratanachu-Ek (27) in 2011 in Thailand were 28%, 16% and 22%, respectively. Arodiwe et al (28) found that 66% of the patients had severe malnutrition, and they also found that stunting was more common than wasting. The prevalence of underweight, stunting and wasting in the current study is 70.9%, 46.1%, and 72.3%, respectively, which is remarkably higher than those of other countries.…”
Section: Discussionmentioning
confidence: 98%